Retención de placenta en vacas lecheras. Concentración de leucocitos circulantes y niveles plasmáticos de cortisol, calcio y magnesio durante el periparto - Silva, J.H. (2016)
In the literature, retained placenta in dairy cows has been associated with decreased neutrophil infiltration in placentomas, mainly due to high cortisol levels during partum, which could decrease the activity of blood neutrophils. Similarly, hypocalcemia could decrease the leukocyte activity, while hypomagnesemia increase it. To deepen these studies, 100 pregnant Holando Argentina cows with no history of retained placenta were sampled. Blood samples were taken a) at 15 days pre-partum, b) within 6 hours post-partum, and c) seven days postpartum. In the three periods, Leukocyte Count, Leukocyte Formula, and serum calcium and magnesium were analyzed; in addition, at b), serum cortisol was analyzed. Only 10 cows had retained placenta. To compare the results, they were divided into two groups: without placental retention and with placental retention. Due to data heterocedasticity, the with placental retention group was divided into two subgroups: neutrophilic and neutropenic. The neutropenic group did not show leukocytosis, neutrophilia and lymphopenia at partum (7090 ± 1129,5 /mm3) (p<0.001), this response was unrelated with cortisolemias observed at b), while the serum calcium was significative lower (p<0.001) in the prepartum of neutropenic group (7,9 ± 0,1 mg/100 mL), which would explain the altered leukocyte response. Hypomagnesemia observed at postpartum of cows with retained placenta can not explain the results evaluated.